Recurrent Pancreatic Pseudocyst Diagnosed 9 Years After Initial Surgical Drainage - Nuño-Guzmán, Carlos M; Arróniz-Jáuregui, José; Gómez-Ontiveros, José I; Hernández-Estrada, Haydée; Estrada-Castañeda, Haydee I; Araiza-Navarro, Juan R; Esparza-Arias, Nereida (JOP. Journal of the Pancreas, 2011)
Context A pancreatic pseudocyst is defined as a collection of pancreatic juice enclosed by a wall of fibrous or granulation tissue which is not lined by epithelium. Acute pseudocysts occur in acute pancreatitis but can be found after an acute exacerbation of chronic pancreatitis. Chronic pancreatic pseudocysts are typically found in chronic pancreatitis but may develop after an occurrence of acute pancreatitis as well. Most acute fluid collections and pseudocysts will show spontaneous resolution while the remaining may persist with or without symptoms, or progress to produce complications. Treatment is indicated for persistent, symptomatic pseudocysts and, in the case of complications. There is no clear consensus regarding the optimal clinical or radiologic follow-up after treatment. Detection of late recurrence is not common, and the possibility of a cystic neoplasm must be ruled out. Case report We report the case of a 67-year-old female patient who was referred to our institution as the result of a pancreatic pseudocyst. The patient had presented a pancreatic pseudocyst 9 years earlier which had been surgically treated by a cystogastrostomy. No additional acute pancreatic episodes occurred. The diagnostic and treatment approach of this unusual late recurrent pancreatic pseudocyst is herein described. Conclusion The unusual late presentation of a recurrent pancreatic pseudocyst requires clinical, laboratory and radiological evaluation. In the present case, the clinical background, amylase fluid levels and tomographic findings were highly suggestive of a pancreatic pseudocyst. Image: A well-circumscribed unilocular pancreatic pseudocyst.